2008
DOI: 10.1159/000124290
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Survivin Expression by Short Hairpin RNA Induces Apoptosis in Human Laryngeal Carcinoma Cells

Abstract: Purpose: The aim of this study was to evaluate the suppression effect of survivin shRNA on the expression of the survivin gene in the human laryngeal cancer cell line Hep-2. Procedures: 60 cases of laryngeal squamous-cell carcinoma (LSCC) and 10 cases of normal laryngeal mucosa were examined using immunohistochemistry to determine whether the expression of survivin correlated with tumorigenesis. Three plasmid vectors of short hairpin RNA (shRNA) specific for survivin were designed and generated. Western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Many preliminary lines of evidence indicate that survivin inhibition by gene therapy (antisense oligonucleotides) and by small molecule inhibitors in head and neck carcinoma cell lines increases the anti‐tumour activity of several cytotoxic and other targeted therapies significantly 5 . Only a very limited number of the reported experiences of survivin inhibition have focused on LSCC cell lines, however 32–34 …”
Section: Discussionmentioning
confidence: 99%
“…Many preliminary lines of evidence indicate that survivin inhibition by gene therapy (antisense oligonucleotides) and by small molecule inhibitors in head and neck carcinoma cell lines increases the anti‐tumour activity of several cytotoxic and other targeted therapies significantly 5 . Only a very limited number of the reported experiences of survivin inhibition have focused on LSCC cell lines, however 32–34 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, survivin overexpression is usually correlated with low apoptotic and high proliferative activities, which favors the survival of cancer cells [17]. Previously, several in vitro studies have demonstrated that inhibition of survivin gene expression could lead to apoptotic induction and growth suppression in human laryngeal carcinoma cells [29,30]. To further determine whether survivin contributes to the apoptotic inhibition and proliferative promotion in laryngeal cancer, we investigated the survivin expression in all LSCCs evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The same results were achieved by transfecting a plasmid-containing survivin shRNA into an OSCC tongue cell line: shRNA inhibited the expression of survivin at both the protein and mRNA level, inhibited cell proliferation via caspase-3 activity induction, and enhanced chemosensitivity to cisplatin [ 115 ]. Survivin shRNA-mediated knockdown suppressed tumor growth and induced apoptosis after transfection into human laryngeal carcinoma cell lines [ 116 ]. Ngan et al [ 117 ] evaluated the responses to oxaliplatin, a third-generation platinum-based chemotherapeutic agent, in two esophageal cancer cell lines, one derived from SCC and one from adenocarcinoma.…”
Section: Gene Therapymentioning
confidence: 99%